Laporan Keuangan BAZNAS di Era Digital 4.0: Tinjauan atas PSAK 109 - Anis Choirun Nisa; Hanifah Indarwati; Siti Muthi’ah; Saiful Anwar (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2021)
This study aims to evaluate the BAZNAS financial statements with PSAK 109 and analyze the factors that affect the quality of BASNAZ's financial statements. This research uses a qualitative descriptive approach, the research method uses content analysis. The object of research in the Salatiga City BAZNAS was with primary data collection techniques derived from interviews with the managers of Salatiga City's BAZNAS in person. Whereas secondary data is obtained through intermediaries generally in the form of notes, empirical evidence, or historical reports that have been compiled in archives (documentary data), whether or not they have been published. The results of the study, after the data was collected and compared with PSAK 109, it can be seen that the Salatiga City BAZNAS 2019 has conducted the preparation of financial statements in accordance with the format contained in PSAK 109, namely single entry. However, there are a number of financial statements that claim to be incomplete in accordance with the format contained in PSAK 109, among others, not including Non-halal funds in their financial statements, which only include assets, liabilities and balance funds. Statements of cash flows and changes in funds BAZNAS Salatiga City are in accordance with PSAK 109 format. Inadequate HR is a factor that causes a lack of conformity in the financial statement format with PSAK 109 format. In addition there are several other factors that can affect the quality of financial statements such as the accounting system which also applies to the use of technology applied in the National Police. The contribution of this research is to provide an explanation of the presentation of financial statements that should be and explain the importance and benefits of digitizing the financial statements of Salatiga BAZNAS.